2007
DOI: 10.1109/tit.2007.907482
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fading, Channel Inversion, and Threshold Scheduling onAd HocNetworks

Abstract: This paper addresses three issues in the field of ad hoc network capacity: the impact of i) channel fading, ii) channel inversion power control, and iii) threshold-based scheduling on capacity. Channel inversion and threshold scheduling may be viewed as simple ways to exploit channel state information (CSI) without requiring cooperation across transmitters. We use the transmission capacity (TC) as our metric, defined as the maximum spatial intensity of successful simultaneous transmissions subject to a constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
283
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(292 citation statements)
references
References 35 publications
8
283
0
1
Order By: Relevance
“…This is because the interference reduces the channel capacity of legal link. At the same time, we can observe that the gap of the average secrecy rate between the scenarios of noncooperative eavesdroppers and cooperative eavesdroppers is becoming narrower with the increasing of / , especially the gap between the upper bound of the average secrecy rate with the exact analytical expression in (9). The reason is that the large-scale fading is gradually becoming the main cause on secrecy performance.…”
Section: Numerical Results and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This is because the interference reduces the channel capacity of legal link. At the same time, we can observe that the gap of the average secrecy rate between the scenarios of noncooperative eavesdroppers and cooperative eavesdroppers is becoming narrower with the increasing of / , especially the gap between the upper bound of the average secrecy rate with the exact analytical expression in (9). The reason is that the large-scale fading is gradually becoming the main cause on secrecy performance.…”
Section: Numerical Results and Discussionmentioning
confidence: 89%
“…From Proposition 1 and the definition of , the average secrecy rate can be expressed as (9), the average secrecy rate at the typical user decreases when the value increases. Also, with the increasing of path loss exponent , the average secrecy rate increases.…”
Section: Corollary 3 the Average Secrecy Rate Is Provided Bymentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of fading, power allocation, and interference cancellation on the outage probability in ad hoc networks is also studied in [9] and [10].…”
Section: Introductionmentioning
confidence: 99%
“…[4], [5]. The fixed transmission distance of d is clearly not a reasonable assumption; however our prior work [1], [6] has shown rigorously that variable transmit distances do not result in fundamentally different capacity results, so a fixed distance is chosen because it is much simpler analytically and allows for crisper insights. Our model does not include fading, but our past work has shown that the effect of fading in the interference-limited regime is only a multiplicative constant; the effect of fading in the energy-limited regime is of interest but it beyond the scope of this work.…”
Section: Introductionmentioning
confidence: 99%